(untitled) (Al-Academy, 2016)
This study deals with the reality of the design of a washing machine automation available in the markets Mahlah.otata importance of this issue is through the development of technological and technical exploited for the benefit of the consumer and always seeking perfection in industrial product through providing comfort to the user and reduce fatigue and the effort and time-saving as well. On this basis, the research aims of this study put the foundations for the development of design automation washer. The boundaries of the study were products company LG producing Sna2012.uahtot this study on five chapters included Allvsal first importance of research and the need for a mechanism in addition to Alchuklh research objectives and Hdodh.ama Chapter II has included previous studies and Alataralnzera and which contained two sections was titled the first design of a washing machine automation, and the second mechanism washer automation work and then ended this chapter Palmahrat.oachtml Chapter III on measures of research and Menhjath.ama Chapter IV has included description and analysis of the samples by the models form the fifth Mhaoralthalil.oagiraalvsal ensure results and conclusions